Analysis of carbon tax efficiency in energy industries of selected EU countries - Hájek, Miroslav; Zimmermannová, Jarmila; Helman, Karel; Rozenský, Ladislav (Energy policy, 2019)
A carbon tax is one of economic policy instruments of environmental protection supposed to contribute to the reduction of greenhouse gas (GHG) emissions. A functional carbon tax aims at incorporating costs for elimination of environmental harm into the pricing decisions. In terms of global climate change, the carbon tax is usually imposed on the production, distribution or consumption of carbon-content fossil fuels. The main aim of the study is to evaluate the carbon tax environmental effectiveness in the energy industries of selected EU countries, namely Sweden, Finland, Denmark, Ireland and Slovenia. To achieve the principal research objective, the multiple panel regression method for the selected variables was used, the synergy of other environmental policy tools being taken into account. Control variables employed were emission allowance price, household final consumption expenditure, corporate investments, solid fuel consumption and renewable energy consumption. The analysis results suggest that the carbon tax in the energy industry is environmentally efficient, an increased tax rate allowing to reduce GHG production, which is statistically significantly affected by the consumption of fossil fuels. Based on the estimated partial regression coefficient (−0.01158), raising the carbon tax by one euro per tonne can cut annual per capita emissions by 11.58 kg. •CO2 tax higher by 1EUR/tonne may decrease the (annual) emissions/capita by 11.58 kgs.•No evidence about partial negative effect of the EUA price on GHG emissions.•Carbon tax more environmentally efficient than EU ETS in a long-term period.•Consumption of fossil fuels and renewables influences CO2 emissions.